Revitalisasi Kelas Kursus Bahasa Arab melalui Pendekatan Variatif dan Edukatif di Madrasah Aliyah Roudlotut Tholibin Balen – Bojonegoro - Latifah, Siti Nurul Aini; Lina Agustina; Layya Nurul Farikah (Yayasan Literasi Altruis Khatulistiwa, 2026)
This Community Service Program (PKM) was carried out to address the low mastery of the Arabic language among students at MA Roudlotut Tholibin Balen, particularly in vocabulary acquisition, grammatical understanding, and learning motivation. These challenges prompted the school to establish an Arabic language course designed for students from grades X to XII as a reinforcement program. Through a formal collaboration between MA Roudlotut Tholibin Balen and Institut Attanwir Bojonegoro, this PKM activity was initiated to improve and revitalize the existing course, which had previously been considered monotonous and lacking significant progress. The main objective of this program was to provide students with theoretical and practical guidance in learning Arabic through engaging, interactive, and needs-based approaches. The activities were conducted once every two weeks, beginning on August 1, 2025, and included sessions covering essential linguistic components such as nahwu, vocabulary enrichment, insyā’, and other language skills. In addition to the core materials, students were introduced to Arabic songs, interactive games, and creative learning techniques to enhance their enthusiasm and motivation.